REFRAMING WRITING INSTRUCTION THROUGH INTEGRATING PROBLEM-BASED LEARNING AND FORMATIVE ASSESSMENT FOR ACADEMIC WRITING AND 4C SKILLS - Andi Patmasari; Agussatriana Agussatriana; Afrillia Anggreni; Dwi Putri; Fadhilah Zamzam; Muhammad Ismail (Universitas Labuhanbatu, 2026)
Purpose – Students' writing and 4C skills (critical thinking, collaboration, communication, and creativity) remain underdeveloped. This is due to the limited use of innovative learning models and formative assessment—an educational process providing feedback during learning—in classrooms. This research examined whether integrating problem-based learning (PBL), an approach using real-world problems, with formative assessment can improve students’ writing. The study also explored how this integration affects their writing and 4C skills.Methodology – The study used a mixed-methods approach with an explanatory sequential design. The sample included fourth-semester students from the Writing in Professional Context course, specifically Class B. Researchers collected performance assessments and interviews and analyzed the data using both quantitative and qualitative methods.Findings – Quantitative results showed that integrating PBL and formative assessment significantly improved students’ writing skills. Qualitative results indicated that this integration also improved writing structure, coherence, diction, and argument development. The integration enhanced writing performance and fostered 4C skills (critical thinking, collaboration, communication, and creativity).Contribution – This research advances writing pedagogy and 21st-century skills by guiding educators to adopt innovative, student-centered learning practices.